2005
DOI: 10.1074/jbc.m411845200
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Receptor in Leishmania Is a Hexokinase Located in the Flagellar Pocket

Abstract: Hb endocytosis in Leishmania is mediated through a 46-kDa protein located in the flagellar pocket. To understand the nature of the Hb receptor (HbR), we have purified the 46-kDa protein to homogeneity from Leishmania promastigote membrane. Purified HbR specifically binds Hb. The gene for HbR was cloned, and sequence analysis of the full-length HbR gene indicates the presence of hexokinase (HK) signature sequences, ATP-binding domain, and PTS-II motif. Four lines of evidence indicate that HbR in Leishmania is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 41 publications
2
75
0
Order By: Relevance
“…invariably utilize macrophages as their exclusive host cells by residing in their phagolysosomes wherein senescent erythrocytes are known to end up for disposal, making available hemoglobin and its degradation products (Chang & Chang, 1985). The loss of heme biosynthetic pathway in these unusual parasites may be explained by the intraphagolysosomal availability of this hemoprotein in abundance coupled with the evolution of an effective mechanism for its uptake by receptor-mediated endocytosis (Krishnamurthy et al, 2005). Whatever the evolutionary scenario may be, the transgenic mutants produced here are of value as a cellular model to study monospecific porphyria, not previously available.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…invariably utilize macrophages as their exclusive host cells by residing in their phagolysosomes wherein senescent erythrocytes are known to end up for disposal, making available hemoglobin and its degradation products (Chang & Chang, 1985). The loss of heme biosynthetic pathway in these unusual parasites may be explained by the intraphagolysosomal availability of this hemoprotein in abundance coupled with the evolution of an effective mechanism for its uptake by receptor-mediated endocytosis (Krishnamurthy et al, 2005). Whatever the evolutionary scenario may be, the transgenic mutants produced here are of value as a cellular model to study monospecific porphyria, not previously available.…”
Section: Resultsmentioning
confidence: 97%
“…The inability of trypanosomatid protozoa to synthesize heme results in their nutritional requirement for hemin, hematin or hemoglobin as a growth factor (Trager, 1974;Chang et al, 1975;Chang & Chang, 1985;Krishnamurthy et al, 2005). Earlier, this deficiency has been delineated genetically by transfecting Leishmania amazonensis with mammalian cDNAs, encoding the 2 nd and 3 rd enzymes of the biosynthetic pathway for tetrapyrroles (Sah et al, 2002) (Cf.…”
Section: Introductionmentioning
confidence: 99%
“…Arabidopsis thaliana hexokinase 1 (AtHXK1) has been shown to play a role in signal transduction, even in the absence of catalytic activity (17). Lastly, a Leishmania HK involved in hemoglobin endocytosis has been found localized to the flagellar pocket (11). These observations suggest that TbHK2 may function in pathways distinct from glucose phosphorylation, providing an area of ongoing research.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, we have shown that Ldgp63 is trafficked via Rab1 dependent conventional secretory pathway in Leishmania (36). Moreover, we have also shown that Leishmania has conserved trafficking pathways like higher eukaryotic cells (37)(38)(39)(40)(41)(42)(43)(44). Thus, it is tempting to speculate that Ldgp63 might exit from ER by Sar1-dependent COPII mediated process.…”
Section: Discussionmentioning
confidence: 99%